The United States Department of Defense Law of War Manual : commentary and critique / edited by Michael A. Newton. - Newton, Michael A., 1962- (Cambridge University Press, 2018)
The United States Department of Defense Law of War Manual: Commentary and Critique provides an irreplaceable resource for any politician, international expert, or military practitioner who wishes to understand the approach taken by the American military in the complex range of modern conflicts. Readers will understand the strengths and weaknesses of US legal and policy pronouncements and the reasons behind the modern American way of war, whether US forces deploy alone or in coalitions. This book provides unprecedented and precise analysis of the US approach to the most pressing problems in modern wars, including controversies surrounding use of human shields, fighting in urban areas, the use of cyberwar and modern weaponry, expanding understanding of human rights, and the rise of ISIS. This group of authors, including academics and military practitioners, provides a wealth of expertise that demystifies overlapping threads of law and policy amidst the world's seemingly intractable conflicts.